Review of social behaviors and cultural reproduction from the perspective of Bourdieu’s Theories practice and reproduction - Dadman, Enayatullah; Aminzai, Wafiullah; Moradi, Masoma (Privietlab, 2025)
This study provides a comprehensive review of social behaviors and cultural reproduction using Bourdieu’s theories of practice and reproduction. Social behaviors and cultural patterns are central to understanding the reproduction of societal structures, yet they often go unexplored regarding power dynamics and individual agency. Bourdieu’s concepts of